Islamic Service Quality and Customer Switching Factor Among Islamic Banks in Yogyakarta Province From Maqasid Syariah Perspective - Krisnanda (MUSLIMPRENEUR : Jurnal Ekonomi dan Kajian Keislaman, 2022)
In the current globalization era, banking faces a number of challenges, including service quality, product development, human resource development, development in information technology, and regulatory aspects. The Financial Services Authority (OJK) has recorded that the sharia finance industry in Indonesia continues to experience positive growth. The development of sharia economy in Yogyakarta Special Province (DIY) is relatively positive, and even the growth of sharia banking sector exceeds that of conventional banking. In line with the increasing number and development of sharia financial institutions, there has to be subsequent efforts to improve the customer service quality, especially in terms of Islamic services. A quality service is considered as an important aspect to build the image of a product. This study aimed to examine of Islamic service quality and customer switching factor in Islamic Banks. The data was collected through a questionnaire distributed to the customers of Bank Syariah Mandiri, Bank Muamalat Indonesia, Bank BNI Syariah, and Bank BRI Syariah in Yogyakarta Special Province. There were 150 respondents involved in this study. The research method used was descriptive analysis with the quantitative approach.The results of this study proved that the Islamic service quality, the assurance dimension has the highest total score, the reliability dimension has the second highest total score, and the complience dimension has the lowest total score. In the customer switching factor, the ethical problems dimension has the highest total score, the pricing dimension has the second highest total score, and the core service failures dimension has the lowest total score.